Design and current status of CONTINT: continuous versus interrupted abdominal wall closure after emergency midline laparotomy - a randomized controlled multicenter trial [NCT00544583] - Rahbari, Nuh Nabi; Knebel, Phillip; Kieser, Meinhard; Bruckner, Thomas; Diener, Markus K.; Voß, Sabine; Rossion, Inga; Büchler, Markus W.; Seiler, Christoph (Trials, 2012)
The optimal strategy for abdominal wall closure has been an issue of ongoing debate. Available studies do not specifically enroll patients who undergo emergency laparotomy and thus do not consider the distinct biological characteristics of these patients. The present randomized controlled trial evaluates the efficacy and safety of two commonly applied abdominal wall closure strategies in patients undergoing primary emergency midline laparotomy.
Gesehen am 22.11.2018